Evaluation result of disaster safety status for Military Hospitals - Nguyen, Nhu Lam; Nguyen, Tien Dung; Tran, Dinh Hung; Ngo, Minh Duc; Tran, Quang Phu; Nguyen, Thai Ngoc Minh; Nguyen, Thanh Chung; Le, Quoc Chieu (Tạp chí Y học Thảm hoạ và Bỏng, 2024)
Aims: To evaluate the level of safety in disasters of a number of strategic and campaign-level military hospitals.Subjects and methods: The surveys were conducted at 9 strategic and campaign-level military hospitals. The hospitals were instructed to establish their own assessment teams and follow the steps outlined in the toolkit for evaluating safe military hospitals in disasters.Results: The structural and non-structural groups had the highest proportion of criteria fully met (85.78%), while the lowest was the group managing operations in emergencies and disasters (38.00%). Regarding the level of safety in disasters, 4 hospitals (44.44%) achieved a high safety level, 5 hospitals (55.56%) achieved a medium level, and no hospital achieved a low safety level.Conclusion: It is necessary to improve the level of safety in disaster military hospitals, especially the criteria related to the management of activities in emergency and disaster situations.